Total parathyroidectomy in a large cohort of cases with hyperparathyroidism associated with multiple endocrine neoplasia type 1: experience from a single academic center - Montenegro, Fabio Luiz de Menezes (2012)
Most cases of sporadic primary hyperparathyroidism present disturbances in a single parathyroid gland and the surgery of choice is adenomectomy. Conversely, hyperparathyroidism associated with multiple endocrine neoplasia type 1 (hyperparathyroidism/multiple endocrine neoplasia type 1) is an asynchronic, asymmetrical multiglandular disease and it is surgically approached by either subtotal parathyroidectomy or total parathyroidectomy followed by parathyroid auto-implant to the forearm. In skilful hands, the efficacy of both approaches is similar and both should be complemented by prophylactic thymectomy. In a single academic center, 83 cases of hyperparathyroidism/ multiple endocrine neoplasia type 1 were operated on from 1987 to 2010 and our first surgical choice was total parathyroidectomy followed by parathyroid auto-implant to the non-dominant forearm and, since 1997, associated transcervical thymectomy to prevent thymic carcinoid. Overall, 40% of patients were given calcium replacement (mean intake 1.6 g/day) during the first months after surgery, and this fell to 28% in patients with longer follow-up. These findings indicate that several months may be needed in order to achieve a proper secretion by the parathyroid auto-implant. Hyperparathyroidism recurrence was observed in up to 15% of cases several years after the initial surgery. Thus, long-term follow-up is recommended for such cases. We conclude that, despite a tendency to subtotal parathyroidectomy worldwide, total parathyroidectomy followed by parathyroid auto-implant is a valid surgical option to treat hyperparathyroidism/multiple endocrine neoplasia type 1. Larger comparative systematic studies are needed to define the best surgical approach to hyperparathyroidism/multiple endocrine neoplasia type 1.